2021
DOI: 10.1080/03007995.2021.1968813
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral Pentasa (prolonged-release mesalazine) in mild-to-moderate ulcerative colitis: a systematic review and meta-analysis

Abstract: Background: Pentasa (prolonged-release mesalazine [5-ASA]) has been available for >30 years as an effective treatment for mild-to-moderate ulcerative colitis (UC). A systematic literature review and meta-analysis was undertaken to provide an up-to-date evaluation of oral Pentasa efficacy and safety for induction and maintenance of remission. Methods: Literature searches were conducted in PubMed, Embase and Cochrane databases, from inception to 02 December 2020. Unpublished studies were also sourced. Meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It is shown that it reduces inflammation of the intestinal mucosa acting locally. It is a safe and well-tolerated medication, with proven efficacy in mild to moderate ulcerative colitis [ 20 ]. In this patient, we used mesalamine to lower the inflammatory burden locally in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that it reduces inflammation of the intestinal mucosa acting locally. It is a safe and well-tolerated medication, with proven efficacy in mild to moderate ulcerative colitis [ 20 ]. In this patient, we used mesalamine to lower the inflammatory burden locally in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The primary pathogenic mechanism for UC involves aberrant activation immune responses, which are important defense guard against pathogenic factors but also culprit of disease progression 8 . Mesalazine stands for the current standard regimen in the remission of mild to moderate disease; however, it necessitates up to 15 years of continuous treatment 9 . Other biological agents, such as antitumor necrosis factor‐α (TNF‐α), anti‐integrin and anti‐interleukin (IL) agents, and the nonbiologic small molecule tofacitinib, can be administered in cases where there is an insufficient response to Mesalazine treatment 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Mesalazine stands for the current standard regimen in the remission of mild to moderate disease; however, it necessitates up to 15 years of continuous treatment. 9 Other biological agents, such as antitumor necrosis factor-α (TNF-α), anti-integrin and anti-interleukin (IL) agents, and the nonbiologic small molecule tofacitinib, can be administered in cases where there is an insufficient response to Mesalazine treatment. 10 Nevertheless, the overall efficacy was limited by high recurrence rate and specific adverse effects.…”
mentioning
confidence: 99%
“…The first-line therapy of UC initiates with mesalamine (5-aminosalicylic acid), which may also prevent CRC development [8]. If this treatment does not sufficiently affect, corticosteroids, immunosuppressive agents, biologics (such as anti-tumor necrosis factoralpha (TNF-α) antibodies, anti-integrin antibodies, antiinterleukin (IL) 12-23 antibodies), and/or non-biologic small molecule tofacitinib may be applied [9].…”
Section: Introductionmentioning
confidence: 99%